2022
DOI: 10.1021/acs.molpharmaceut.2c00466
|View full text |Cite
|
Sign up to set email alerts
|

3D-Printed Integrated Ultrasonic Microneedle Array for Rapid Transdermal Drug Delivery

Abstract: Transdermal drug delivery (TDD) is an attractive alternative to oral and hypodermic injection drug administration, and is poised to increase its impact on medicine and pharmaceutical design. Microneedles (MNs) are a new minimally invasive TDD method widely used in medicine and cosmetology. MNs create a microscale channel from the stratum corneum to the dermis and enable drug delivery of hydrophilic and macromolecular into the skin. Although MNs allow different drugs to penetrate the stratum corneum, they canno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 30 publications
(48 reference statements)
1
10
0
Order By: Relevance
“…In comparison to conventional manufacturing methods, 3D printing reduces labor and equipment costs in the production process. Moreover, it optimizes the utilization of raw materials, minimizes waste, and lowers production costs. ,, Additionally, 3D printing technology facilitates customized production of microneedles tailored to individual requirements. , By adjusting design parameters, the shape, size, and structure of microneedles can be easily modified to meet diverse clinical needs. , It also enables the realization of complex structures and integration of multiple functions in microneedles. By incorporating intricate details and functionalities during the design and printing process, the performance and efficacy of microneedles can be enhanced to cater to a wider range of clinical requirements. Furthermore, the utilization of renewable and biodegradable materials in printing further enhances the sustainability of microneedles while minimizing their environmental impact. , Additionally, as a versatile medical tool, microneedles must be capable of accommodating diverse treatment needs and application scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to conventional manufacturing methods, 3D printing reduces labor and equipment costs in the production process. Moreover, it optimizes the utilization of raw materials, minimizes waste, and lowers production costs. ,, Additionally, 3D printing technology facilitates customized production of microneedles tailored to individual requirements. , By adjusting design parameters, the shape, size, and structure of microneedles can be easily modified to meet diverse clinical needs. , It also enables the realization of complex structures and integration of multiple functions in microneedles. By incorporating intricate details and functionalities during the design and printing process, the performance and efficacy of microneedles can be enhanced to cater to a wider range of clinical requirements. Furthermore, the utilization of renewable and biodegradable materials in printing further enhances the sustainability of microneedles while minimizing their environmental impact. , Additionally, as a versatile medical tool, microneedles must be capable of accommodating diverse treatment needs and application scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Sonophoresis can provide an extra driving force to improve drug transport via MNs and reduce tissue damage. [ 121 ] These devices and MNs are promising delivery methods for TCI, and their combination is expected to complement each other. In the future, it could be necessary to find ways to combine these devices to achieve low‐cost and efficient delivery.…”
Section: Improvement Of Mn‐mediated Nucleic Acid Vaccinationmentioning
confidence: 99%
“…Microneedles (MN) have emerged as a novel drug delivery method , that can penetrate the stratum corneum of the skin in a minimally invasive manner without stimulating the subcutaneous tissue and blood vessels to complete drug delivery. Compared with other delivery methods, MN has the advantages of being painless, having no bleeding or infection, reduced dosage, improved efficiency of drug delivery, and being able to precisely locate specific areas of the skin, , making it easy to self-manage and improve patient compliance. Although several studies have reported on the transdermal delivery of FNS, they have encountered challenges in adapting to various rough and irregularly shaped skin environments. This resulted in easy detachment from the skin surface and needle breakage.…”
Section: Introductionmentioning
confidence: 99%